LINEARITY TEST ANALYSIS OF AIRCRAFT RADIATION OUTPUT X-RAY FLUOROSCOPY - Harianto, Bambang; Kardaji, Muhammad (MSJ : Majority Science Journal, 2023)
The number or intensity of X-ray photons produced correlates with the increase in tube current per time (mAs), which affects the image density on the final film. To ensure the consistency of the increase in X-ray radiation output and the Linear Coefficient of X-ray radiation output, is within the tolerance limits specified in PERKA BAPETEN Regulation Number 9 of 2011. The aim of this research is to determine the linearity of the X-ray Fluoroscopy radiation output in one of the houses. Jakarta sick. The method used is an experimental approach with a quantitative model. Measurement of radiation output using a PM1610 Personal Dosimeter on a Fluoroscopy aircraft. The results of measuring the linearity of X-ray radiation output with voltage variations of 40 kV, 50 kV, 60 kV, 70 kV show that the value of the Linearity Coefficient (CL) is (0.08 ; 0.06 ; 0.09 ; 0.07). So it can be said that the X-Ray Fluoroscopy equipment is in good condition because the CL value obtained in this study is below the Tolerance Limit Value according to PERKA BAPETEN Number 9 of 2011, namely CL ≤ 0.1 or ≤10%. This research can be carried out as a reference in further research